Peran Badan Penyelesaian Sengketa Konsumen dalam Pengawasan Klausula Baku di Kota Palembang - Sri Turatmiyah; Arfianna Novera (Fakultas Hukum Universitas Islam Indonesia, 2017)
This research studies the role of BPSK (Badan Penyelesaian Sengketa Konsumen or Costumer's Conflict Resolution Board) in Palembang city in supervising the standard clause and any hindrances in that supervision. This research used the juridical-empirical research method supported by the regulatory approach and case approach. The result of the research showed that the role of BPSK in the supervision of inclusion of standard clause until recently is not applied well. This is due to BPSK simply waits for any complaints from customers and there is no any follow up from BPSK. Meanwhile, the hindrances in the supervision of standard clause are related to the absence of the regulation of implementation as amended in Article 52 letter (e) Law of Customer Protection. BPSK is not a judicial institution, and the operational cost of BPSK is burdened by local budget (APBD) coming from the customers, business actors and government that have a different culture.